Genetic dissection of sympatric populations of brown planthopper, Nilaparvata lugens (Stl), using DALP-PCR molecular markers - Abdul Latif, M.; Mohd Rafii, Yusop, Assoc. Prof. Dr.; M. S., Mazid; Md Eaqub, Ali; Ahmed, Faheem; M. Y., Omar; Tan, Soon Guan, Prof. Dr. (Hindawi Publishing Corporation, 2013)
Link to publisher's homepage at http://www.hindawi.com/